EDUPRENEUR: INDUSTRIAL COMPETITIVENESS AS EXTERNAL FACTORS TOWARDS MALAYSIA PRIVATE HIGHER EDUCATION INSTITUTION PERFORMANCE - Ahmad, Norhaidah; Mahmud, Nurazree; Marmaya, Najihah Hanisah (Jurnal ’Ulwan, 2022)
The purpose of this conceptual paper is to browse the relationship of Theory of Industrial Competitiveness as External Factors towards Malaysia Private Higher Education Institution Performance from the Edupreneur perspective. Edupreneur or education entrepreneur, is a person within the education institution who take hands on responsibility in creating and developing program, product, service and /or technology for the enhancement of learning consistent with the stated goals of and supported by organization. They also act as the unit of analysis, as they involve in survival on Private Higher Education Institution in Malaysia directly. Therefore, their views on factors involved should be highlight. The Industrial Competitiveness Theory is derived from theory of Sustainable Competitive Advantage on Private Higher Education .However, due to research gap and suitability with problem in hand, only three factors will be highlight in this article which are Competition, Innovation and Industrial Linkage. The elements will be cross check with Private Higher Education Institution Performance Measurement which are Academic Effectiveness, Rating Criteria, Research Capacity & Capability and Financial Performance. As for practical implication, this conceptual paper will help Ministry of Higher Education and Malaysia Private Higher Education Institution for determining their path that should be taken especially on post-Covid-19 Pandemic that hit Malaysia recently. It also helps the Practitioners in Malaysia to determine the strategies to enhance the Sustainable Competitive Advantage and survive in the stiff competition in Malaysia.